Selection of patients with severe pelvic fracture for early angiography remains controversial - Alfici Ricardo (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2009)
Abstract Background Patients with severe pelvic fractures represent about 3% of all skeletal fractures. Hemodynamic compromise in unstable pelvic fractures is associated with arterial hemorrhage in less than 20% of patients. Angiography is an important tool in the management of severe pelvic injury, but indications and timing for its performance remain controversial. Methods Patients with major pelvic fractures [Pelvic Abbreviated Injury Score (AIS) ≥ 3] admitted to two high volume Trauma Centers from January 2000 to June 2005 were identified and divided into two groups: Group I patients did not undergo angiography, Group II patients underwent angiography with/without embolization. Demographics, hemodynamic status on admission, concomitant injuries, Glasgow Coma Scale (GCS), Injury Severity Score (ISS), pelvic AIS, blood requirement before and after angiography, arterial blood gases and mortality were evaluated. Patients with an additional reason for hemodynamic instability were excluded. Results Charts of 106 patients were retrospectively reviewed. Twenty nine patients (27.4%) underwent angiography. Bleeding vessel embolization was performed in 20 (18.9%) patients. Patients who underwent angiography had a significantly higher pelvic AIS and a lower Base Excess level on admission. A blood transfusion rate of greater than 0.5 unit/hour was found to be a reliable indicator for early angiography. Conclusion A high pelvic AIS, amount of blood transfusions and decreased BE level should be considered as an indicators for early angiography in patients with severe pelvic injury.